Evaluation of synthetic‐gene recombinant LipL32 antigen for IgM ELISA detection of Leptospira infection - Widiastuti, Dyah; Paramita, Dewi Kartikawati; Murwanti, Retno; Kusrini, Ina; Wijayanti, Nastiti; Haryanto, Aris (Indonesian Journal of Biotechnology, 2025)
Leptospirosis presents with nonspecific clinical features and requires time‐consuming laboratory tests for gold standard diagnosis. This study aims to design and characterize the recombinant LipL32 from synthetic gene and assess its performance as an antigen for detecting leptospirosis. The antigen was developed by cloning the LipL32 gene conserved portion of Leptospira interrogans serovar Icterohaemorrhagiae strain Langkawi. The immunoinformatic was used to characterize the developed rLipL32. Western blot results using anti‐histidine revealed a band of rLipL32 protein at ~40 kDa. Subsequently, it was used to examine the IgM antibody on human sera by using ELISA. The IgM‐LipL32 ELISA was evaluated using 67‐positive and 25‐negative sera and compared with a commercial ELISA. With a cut‐off value of 0.8, it showed 85.7% sensitivity, 83.3% specificity, a 48% positive prediction value (PPV), and 97% negative prediction value (NPV), indicating modest performance compared to existing commercial kits. The rLipL32 is a potential antigen for detecting IgM using ELISA; however, for use in low incidence areas, a confirmation test is crucial.